mTOR inhibition prevents epithelial stem cell senescence and protects from radiation-induced mucositis - Iglesias-Bartolome, Ramiro (2012)
The integrity of the epidermis and mucosal epithelia is highly dependent on resident self-renewing stem cells, which makes them vulnerable to physical and chemical insults compromising the repopulating capacity of the epithelial stem cell compartment. This is frequently the case in cancer patients receiving radiation or chemotherapy, many of whom develop mucositis, a debilitating condition involving painful and deep mucosal ulcerations. Here, we show that inhibiting the mammalian target of rapamycin (mTOR) with rapamycin increases the clonogenic capacity of primary human oral keratinocytes and their resident self-renewing cells by preventing stem cell senescence. This protective effect of rapamycin is mediated by the increase expression of mitochondrial superoxide dismutase (MnSOD), and the consequent inhibition of ROS formation and oxidative stress. mTOR inhibition also protects from the loss of proliferative basal epithelial stem cells upon ionizing radiation in vivo, thereby preserving the integrity of the oral mucosa and protecting from radiation-induced mucositis.